Treating Gnathic form of Mesial Occlusion in Early Adolescence Patients: A Clinical Trial - Hai, Le Thi Thu; Hong, Minh Nguyen Thi; Le, Quỳnh Anh (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of the study was to evaluate the early and late results of the non-surgical orthopedic treatment efficiency in 12–14 years old children with the gnathic forms of mesial occlusion by the dentoalveolar compensation utilizing a permanent device with a palatal expanding screw. METHODS: The study enrolled 26 patients aged 12–14 years who underwent orthopedic treatment by the dentoalveolar compensation using a permanent device with a palatal expanding screw. Late treatment results aged 4–6 years were analyzed for 21 patients by cephalometric indices, five patients were excluded from the study due to change of residence. The comparison group included 20 patients of the same age and diagnosis who received orthopedic treatment with a face mask. RESULTS: The method of treatment utilizing a permanent apparatus with a palatal expanding screw showed better results than the facemask therapy. More pronounced changes of the general growth vector of the facial skeleton toward the maxilla normalization were noted. The anteroposterior relations between the jaw bases were normalized, the normal position of the upper and lower incisors was achieved, a stable interincisal angle was formed, and the aesthetics of the facial profile significantly improved. CONCLUSIONS: Using a fixed apparatus with a palatal expanding screw has significantly improved patients’ morphological, physiological, and esthetic performance. The evaluation of late results (from 4 to 6 years) showed normal development of the dentistry system in 90.5% of cases that allowed avoiding surgical intervention in these patients after the end of skeletal growth.